Bacteria-Inspired Synthesis of Silver-Doped Zinc Oxide Nanocomposites: A Novel Synergistic Approach in Controlling Biofilm and Quorum-Sensing-Regulated Virulence Factors in Pseudomonas aeruginosa - Abirami Karthikeyan; Manoj Kumar Thirugnanasambantham; Fazlurrahman Khan; Arun Kumar Mani (Antibiotics)
Multidrug-resistant Pseudomonas aeruginosa infections pose a critical challenge to healthcare systems, particularly in nosocomial settings. This drug-resistant bacterium forms biofilms and produces an array of virulent factors regulated by quorum sensing. In this study, metal-tolerant bacteria were isolated from a metal-contaminated site and screened for their ability to synthesize multifunctional nanocomposites (NCs). Rapid color changes in the reaction solution evidenced the biotransformation process. The potent isolated Bacillus cereus SASAK, identified via 16S rRNA sequencing and deposited in GenBank under accession number MH885570, facilitated the microbial-mediated synthesis of ZnO nanoparticles and silver-doped ZnO NCs. These biogenic nanocomposites were characterized using UV-VIS-NIR spectroscopy, FTIR, XRD, zeta potential, HRTEM, FESEM, and EDX analyses. At a sub-MIC concentration of 100 µg/mL, 2% Ag-ZnO NCs effectively inhibited virulent factor production and biofilm formation in P. aeruginosa without affecting bacterial growth. Notably, there was a significant reduction in violacein pigment (96.25%), swarming motility, and pyocyanin concentration (1.87 µg/mL). Additionally, biofilm formation (81.1%) and EPS production (83.9%) using P. aeruginosa were substantially hindered, along with reduced extracellular protease activity, as indicated by zone formation (from 2.3 to 1.8 cm). This study underscores the potential of Ag-ZnO NCs as promising agents for combating quorum sensing-mediated virulence in chronic infections caused by multidrug-resistant P. aeruginosa.